Neo-Schumpeterian growth theory: Missing entrepreneurs results in incomplete policy advice - Magnus Henrekson; Dan Johansson (Örebro University School of Business, 2025)
The neo-Schumpeterian growth models, which appeared in the early 1990s, have ostensibly reintroduced the entrepreneur into mainstream growth theory. However, we show that by ignoring genuine uncertainty and by assuming that profits follow an objectively true and ex ante known probability distribution, the entrepreneur is made redundant. Thus, the theory fails to exhaustively explain innovation, the role of ownership competence, profits, the function of financial markets, wealth and income distribution, and, ultimately, economic growth. These shortcomings risk leading to erroneous or overly narrow policy conclusions by overestimating the importance of supporting R&D investments. Rather, the presence of genuine uncertainty forms a fundamental theoretical basis for the importance of new venture creation as a source of innovation-driven growth; entrepreneurs must establish and expand firms to capture the subjectively perceived profit opportunities. Therefore, tax policy is decisive for the commercialization and dissemination of innovations by providing incentives to uncertainty-bearing, not only for entrepreneurs, but also for intrapreneurs and financiers taking an active part in the governance and development of firms based on innovations characterized by genuine uncertainty. Furthermore, taxation can distort the evolutionary selection of innovations and firms, for instance, by taxing owners and firms differently.
Keywords: B40; O10; O30; 330; creative destruction; economic growth; entrepreneur; entrepreneurship policy; innovation; judgment; Knightian uncertainty